Pentingnya Mengembangkan Media Pembelajaran Berbasis Argumen Driven Inquiry (ADI) - Melinda, Sarah; Fuadiyah, Sa’diatul (ALSYS, 2023)
21st century learning is required to always be able to adapt to the times and apply 4C abilities. But in fact, the learning process tends to be still teacher-centered, the learning media used are also still not varied and students have not used 4C abilities in learning. This causes students to be passive, monotonous, and bored. The innovation of learning media based on Argument Driven Inquiry (ADI) is expected to be able to increase students' 4C abilities and learning motivation. Viruses are material that is difficult for students to understand, because many foreign terms are used. The purpose of this study was to analyze the need to develop learning media based on Argument Driven Inquiry (ADI) on Virus material. The method used is descriptive research and literature study. Types of data collection from the results of observations of the distribution of questionnaires to students and teachers as well as the results of the Student Daily Assessment. Based on the results of observations made 100% of teachers agree in the development of biology learning media based on Argument Driven Inquiry (ADI). A total of 68% of students are happy to carry out discussion activities in biology learning and 61.11% of students are happy to investigate a problem in biology material. The development of ADI-based biology learning media is one of the alternative media in the learning process in the 21st century as teaching materials, practical and technological developments in accordance with the demands of the times. ADI-based learning media will increase students' ability to communicate, collaborate, and critical thinking.